Computational stylometry: predicting the authorship of investment arbitration awards - Daniel Behn (Edward Elgar Publishing, 2020)
Featuring contributions from a diverse set of experts, this thought-provoking book offers a visionary introduction to the computational turn in law and the resulting emergence of the computational legal studies field. It explores how computational data creation, collection, and analysis techniques are transforming the way in which we comprehend and study the law, and the implications that this has for the future of legal studies.